IMPLEMENTASI METODE PEMBELAJARAN KOOPERATIF TIPE STAD PADA MATA PELAJARAN PAI DI SMP BOARDING SCHOOL JABAL RAHMAH MULIA - Nabilah Nurfitri; Nurman Ginting (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
The STAD cooperative learning method is being applied in Islamic Religious Education (PAI) at Jabal Rahmah Mulia Boarding School Middle School. STAD is known for fostering student cooperation and active participation in learning. This research aims to assess how STAD is used in PAI and its impact on students' social interactions, religious engagement, and academic performance. Data collection methods include classroom observations, teacher interviews, and curriculum document analysis.Students actively collaborate in teams, contributing to their peers' learning and enhancing their grasp of religious concepts. However, this research also highlights challenges in implementing STAD, such as time management and the teacher's role in managing student groups. This study enhances our understanding of how cooperative learning methods can improve the teaching and learning of religious subjects in a boarding school setting.The findings of this research can serve as a valuable guide for other boarding schools looking to implement STAD to enhance students' understanding of religion, develop social skills, and improve academic achievements.